2022
DOI: 10.31083/j.rcm2304120
|View full text |Cite
|
Sign up to set email alerts
|

Relative Risk of Cardiovascular Mortality in Breast Cancer Patients: A Population-Based Study

Abstract: Aims:To investigate the risk of cardiovascular disease (CVD) mortality in breast cancer patients compared with the general female population. Methods: Data was retrieved from the Surveillance, Epidemiology, and End Results database. 924,439 female breast cancer patients who were at the age of follow-up ≥30 years and diagnosed during 1990-2016 as well as the aggregated general female population in the US were included. Using multivariable Poisson regression, we calculated incidence rate ratios (IRRs) of CVD mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We suppose this is related to the following circumstances: the model was primarily designed for those who received anthracycline therapy, and younger age at diagnosis is a significant risk factor, at least for pediatric patients on anthracycline therapy [63]. Chinese researchers showed that the risk of CVD mortality was increased among breast cancer patients at the age of follow-up 30-64 years and was mainly activated by heart diseases [7]. In addition, predictors are unequal by weight and significance within the hierarchy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suppose this is related to the following circumstances: the model was primarily designed for those who received anthracycline therapy, and younger age at diagnosis is a significant risk factor, at least for pediatric patients on anthracycline therapy [63]. Chinese researchers showed that the risk of CVD mortality was increased among breast cancer patients at the age of follow-up 30-64 years and was mainly activated by heart diseases [7]. In addition, predictors are unequal by weight and significance within the hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that BC survivors are three times more likely to develop heart failure (HF) within five years of cancer diagnosis than the general population [6]. According to Chinese researchers, the most vulnerable period is 30-64 years, and the risk peaks within the first months after diagnosis [7]. This worrisome trend is mainly explained by the cardiotoxic effects of chemo-and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that BC survivors are three times more likely to develop heart failure (HF) within 5 years of cancer diagnosis than the general population [6]. According to Chinese researchers, the most vulnerable period for cardiovascular events development in BC patients, including death, is 30-64 years, it has been observed that the risk peaks usually within the first few months after diagnosis [7]. Сardiovascular complications in cancer patients include coronary artery disease, hypertension, QT prolongation, arrhythmias, stroke, peripheral arterial disease, valvular heart disease, pericardial disease, and venous thromboembolism.…”
Section: Introductionmentioning
confidence: 99%